Multisystem inflammatory syndrome in adults: Comparison with other inflammatory conditions during the Covid-19 pandemic. (January 2023) - Auger, Nathalie; Bégin, Philippe; Kang, Harb; Lo, Ernest; Brousseau, Émilie; Healy-Profitós, Jessica; Potter, Brian J.
Abstract: Background: Multisystem inflammatory syndrome in adults (MIS-A) is an increasingly recognized complication of Covid-19. We assessed risk factors, clinical characteristics, and outcomes of patients with MIS-A compared with other inflammatory conditions. Methods: We analyzed a cohort of patients ≥21 years hospitalized with MIS-A in Quebec, Canada between February 2020 and March 2021. We included comparison groups that share symptomatology or pathophysiology with MIS-A, including Kawasaki disease, toxic shock syndrome, and other Covid-19 complications. We examined characteristics of men and women at admission, and identified preexisting factors associated with MIS-A through odds ratios (OR) and 95% confidence intervals (CI) from adjusted logistic regression models. Results: Among 22, 251 patients in this study, 52 had MIS-A, 90 Kawasaki disease, 500 toxic shock syndrome, and 21, 609 other Covid-19 complications. MIS-A was associated with an elevated risk of respiratory failure compared with Kawasaki disease (OR 7.22, 95% CI 1.26–41.24), toxic shock syndrome (OR 4.41, 95% CI 1.73–11.23), and other Covid-19 complications (OR 3.03, 95% CI 1.67–5.50). Patients with MIS-A had a greater risk of cardiac involvement, renal failure, and mortality. The data pointed towards sex-specific differences in presentation, with more respiratory involvement in women and cardiac involvement in men compared with patients that had other Covid-19 complications. Except for allergic disorders and cancer, prior medical risk factors were not associated with a greater likelihood of MIS-A. Conclusions: Patients with MIS-A have an elevated risk of mortality compared with other inflammatory conditions, with women having a predominance of respiratory complications and men cardiovascular complications. Highlights: Clinical outcomes of MIS-A have yet to be compared with other inflammatory disorders. Respiratory complications are more common in women with MIS-A. Cardiovascular complications are more frequent in male patients with MIS-A. Outcomes of MIS-A differ from other inflammatory diseases and may be sex-specific.